The Lithuanian Folk Couplets: On This Side of the Permissible Laughter and Beyond - Stundžienė, Bronė (Tautosakos darbai, 2020)
The article deals with folk couplets (Lith. pl. talalinės) – an underresearched peripheral genre of the Lithuanian folklore. This genre includes short, mostly one stanza-long comic songs that frequently deal with obscene topics and use unquotable vocabulary. This unadvertised folk poetry provisionally dates back to the middle of the 19th century, when its first publications appeared. This genre of folksong attributed to the popular culture of laughter has been always marginalized in relation to the traditional culture. Therefore, the article presents an analysis of this ill-repute frivolous folksong genre, touching upon various aspects of its functioning. The main problem under investigation is, why couplets with no recognized positive value have been so popular among certain groups of the village community (especially young people), and on what grounds this essentially merry and playful folkloric communication has been carried on, bearing in mind that this process is actually not over even today. The development of the Russian частушка as a special instrument of communication and its meaning in the scholarly discourse is also taken into consideration, as well as possible influence of these Russian couplets upon their Lithuanian counterparts. The analysis of talalinės is based upon materials from the Lithuanian Folklore Archives and various publications. Firstly, the article gives an outline of the meager publication and research history of this genre, noting that for a long time these couplets have been made into a certain kind of the sociocultural taboo even in the sphere of scholarly investigation. Right from the beginning of its publication in the second half of the 19th century and throughout the Soviet times, this genre was ignored as having no artistic (or esthetic) value, which was the only criterion applied to the folklore appreciation during that period. However, the first half of the 20th century could be considered the “golden age” in terms of the public spread of these couplets: when the Lithuanian radio started broadcasting, these comic folklore pieces found their way into its program, immediately gaining huge public approval. However, performance only of couplets with appropriate contents was allowed; particularly those dealing with political or obscene topics had to be avoided. The reader is reminded about a historical case from the interwar period, when public distribution of proverb collection edited and published in 1934 by the famous writer Vincas Krėvė-Mickevičius was prohibited, since it contained 300 of obscene texts, which caused significant restrictions to the availability of this publication. A similar misfortune had somewhat earlier befallen the Latvian colleagues publishing a volume of “dirty” Latvian folksongs and other folklore. Such censorship was related to the rigorous program of fostering the national morality of the time that was introduced by the government. However, the authorities did not interfere with collecting of the obscene folklore for the archiving purposes. Therefore, big amounts of folklore material attributed to the culture of laughter were collected especially in the interwar period. Further reviewing of the history of talalinės elucidates the connections between these songs thriving in the 19th – the first half of the 20th century and the humorous poetry created by the contemporary poets, as well as the newly formed folksong genres related to it. The author presents a wide field of miscellaneous relations evolving around this form of folklore. She pays attention to the sarcastic way of caricaturing used in these couplets, when for the purposes of fun-making the outdated popular customs and beliefs are critically targeted, made fun of and vulgarized using obscene vocabulary. Discussion of the essential peculiarities of the talalinės pattern, among other things, elucidates two main tendencies in the thematic canon of this genre. One part of these couplets simply treats the members of the native community and their relationships in a humorous way, as if observing them through a sarcastically distorting comical lens. These cutting couplets mock people from the immediate surroundings, making fun of them as if having previously sorted them into groups according to various characteristics. These include: 1) age groups (making fun of the things that are well-suited to the young but ill-suited to the old, and vice versa), 2) social status (gibing at relations between people from different social classes, like landlords and farmhands, as well as those not engaged in agriculture, like craftsmen, particularly tailors, shoemakers, blacksmiths, but also musicians, priests, nuns, etc.), 3) the alleged or true foreigners, distinguished on the grounds of belonging to a different religious or ethnic group, or characterized by different behavior (however, certain “foreign” character may be attributed to nearly everyone that comes from another community, including a neighboring village or some further locality in Lithuania). According to the second provisionally distinguished type of the talalinės pattern, their thematic scope narrows considerably: these couplets focus on man as a physical creature, an on the human body, or rather, on its lower part. Such couplets are especially fond of the nonstandard – obscene or scatological – vocabulary. Obscene couplets create scenes of essentially similar kind, namely, describing sexual intercourse and the private parts, and using exclusively ribald vocabulary that is usually banned from the public discourse. These quatrains present a wide range of erotic improvisations – from foul suggestions to the harshest obscenities. However, the author concludes that this kind of comic, even obscene speech employed in the couplets is of carnival nature (to use the term by the Russian culture researcher Mikhail Bakhtin): that is, when the temporarily assembled social group aims at entertainment and by common consent decides to ignore the social norms, each participant experiences a special kind of communal unity and belonging. Having crossed the established line, the creator-performer-listener of these couplets feels free both from the public reaction and from the entrenched ideology, and experiences an overwhelming sense of freedom. Such transgression is supplemented by compromise (a certain concession in terms of individual moral principles that are temporarily abandoned for the sake of participating in the game, usually obscene, proposed by the talalinė), and it allows the addressee and the addresser to become equal members of the same group. This is a special mode of folklore communication. Having compared the Lithuanian talalinė with the outwardly related Russian частушка, the author concludes that in spite of certain coincidences, the Lithuanian couplets were composed and structurally arranged independently from their Russian counterparts. However, the most important thing is that the Lithuanian talalinė, recorded for the first time in the second half of the 19th century, presented an alternative for the old folksong, and continued to exist / keeps existing alongside the folksong, abstaining from dismantling its traditional canon, although occasionally making fun of it.
Keywords: folk couplet (Lith. talalinė, Ru. частушка); culture of laughter; obscenity; the comic; transgression; communication